A Five-Year Data Report of Long-Term Central Venous Catheters Focusing on Early Complications - Harald Lenz; Kirsti Myre; Tomas Draegni; Elizabeth Dorph (Anesthesiology Research and Practice)
Background. Long-term venous access has become the standard practice for the administration of chemotherapy, fluid therapy, antibiotics, and parenteral nutrition. The most commonly used methods are percutaneous puncture of the subclavian and internal jugular veins using the Seldinger technique or surgical cutdown of the cephalic vein. Methods. This study is based on a quality registry including all long-term central venous catheter insertion procedures performed in patients >18 years at our department during a five-year period. The following data were registered: demographic data, main diagnosis and indications for the procedure, preoperative blood samples, type of catheter, the venous access used, and the procedure time. In addition, procedural and early postoperative complications were registered: unsuccessful procedures, malpositioned catheters, pneumothorax, hematoma complications, infections, nerve injuries, and wound ruptures. The Seldinger technique using anatomical landmarks at the left subclavian vein was the preferred access. Fluoroscopy was not used. Results. One thousand one hundred and one procedures were performed. In eight (0.7%) cases, the insertion of a catheter was not possible, 23 (2.1%) catheters were incorrectly positioned, twelve (1.1%) patients developed pneumothorax, nine (0.8%) developed hematoma, and three (0.27%) developed infection postoperatively. One (0.1%) patient suffered nerve injury, which totally recovered. No wound ruptures were observed. Conclusions. We have a high success rate of first-attempt insertions compared with other published data, as well as an acceptable and low rate of pneumothorax, hematoma, and infections. However, the number of malpositioned catheters was relatively high. This could probably have been avoided with routine use of fluoroscopy during the procedure.